Implementasi Prinsip Kesetaraan Pada Masa Kepemimpinan Umar Bin Khattab - Fisari, Dinda Harum; Amelia, Rikha; Djasuli, Mohamad (CV. ITTC INDONESIA, 2022)
The principle of equality is the principle of equal and fair treatment in fulfilling the rights of interested parties that grow based on applicable agreements and regulations. Equality can be interpreted as a balanced, equal or equal position for both parties. Islam is a religion that guides the liberation of human values, which from the beginning has tried to instill equality at the time of its revelation. This principle of equality was once applied during the leadership of Umar bin Khattab. During the leadership of Umar bin Khattab, he was famous for his justice in upholding the truth without discrimination. The Medina government during Umar's leadership could guarantee the rights of every citizen by equalizing subordinates and superiors, rulers and people alike without discrimination. This article aims to find out the implementation of the principle of equality during the leadership of Umar bin Khattab. The article research method is descriptive analysis. Leadership in the Qur'an is associated with explanation and guidance to the truth. A leader is not allowed to commit injustice. In Islam it has been proven that the importance of leadership activities after the death of His Majesty the Apostle. So that given the focus and excellence in lifting the Companions to be used as a substitute in leading Muslims. Muslims should not leave without a leader, the caliph Umar bin Khattab has perfected the equality that was practiced by Rasulullah SAW and Caliph Abu Bakar. This can be seen from Umar's role and procedures in realize equality plans in the form of social security and social services.